Analisis dan Simulasi Rekayasa Lalu Lintas Untuk Mengurangi Kemacetan Pada Simpang Tak Bersinyal - Noto Royan; Muhammad Hijrah Agung Sarwandy; Marice Agustini; RAS Delima Amanda Putri; Ahmad Dinar Alamsyah (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2026)
Traffic conflicts frequently occur at intersections. Unsignalized intersections are more prone to traffic conflicts than signalized intersections. Intersection performance is a key factor in determining the most appropriate measures to optimize intersection functionality. One unsignalized intersection in Palembang that frequently experiences traffic congestion is the section of Dr. M. Isa Street and Letda Abdul Rozak Street. This study aims to analyze intersection performance using the 2023 PKJI and VISSIM software to help simulate the most effective traffic engineering measures to reduce congestion. Analysis of data using the 2023 PKJI method yielded a queue probability of 39.36% –77.84%, a degree of saturation of 0.99, and an intersection delay of 18.58 seconds per vehicle. Based on the intersection performance analysis, a poor service level was identified. A highly effective traffic engineering alternative to address the poor intersection performance involves implementing a right-turn ban for vehicles on Dr. M. Isa Road (Toward Veteran) and Letda Abdul Rozak Road. The intersection performance analysis yielded a queue probability of 11.36%–25.40%, a degree of saturation of 0.51, and an intersection delay of 10.09 seconds/vehicle. The VISSIM simulation yielded a queue length of 0 meters and a maximum vehicle delay of 11.14 seconds/vehicle. With the implementation of the traffic engineering alternative prohibiting right turns, the intersection experienced an improvement in service level due to a reduction in queue length and vehicle delay.